Water-absorbent resin and waterproofing material
Patent Information
- Application Number
- JP2021511970
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-27
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2040-03-27
Smart Images

Figure 0007633929000002 
Figure 0007633929000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-absorbent resin and a water-stopping material. [Background technology]
[0002] In recent years, water-absorbent resin particles have been widely used in various fields, such as for sanitary materials such as paper diapers and sanitary products, for agricultural and horticultural materials such as water-retaining materials and soil improvement materials, and for industrial materials such as water-stopping materials for cables and dew condensation prevention materials. As types of water-absorbent resin particles used for such purposes, for example, hydrolyzates of starch-acrylonitrile graft copolymers, neutralized products of starch-acrylic acid graft copolymers, saponified products of vinyl acetate-acrylic acid ester copolymers, partially neutralized products of polyacrylic acid, etc. In general, the performance required for water-absorbent resin particles includes high water absorption amount, excellent water absorption speed, high swelling performance, and a suitable median particle size according to the purpose.
[0003] Of these, the cable waterstop material is, for example, a material in which water-absorbent resin particles are fixed between two or more liquid-permeable sheets, if necessary, using an adhesive or the like, and demand for the material is increasing with the development of the electrical and communication industries. The cable waterstop material is used to wrap and protect the center of a power cable or an optical communication cable, and the outer periphery is further covered with a material such as rubber to form the cable. When the outer material of a power cable or an optical communication cable deteriorates and moisture leaks through cracks that occur and reaches the center of the cable, this leads to a drop in power and communication noise. To prevent this, the cable waterstop material absorbs water and swells to create pressure inside the cable, thereby preventing water from reaching the center of the cable.
[0004] Water-absorbing resins used in water-stopping materials for power cables and communication cables are required to have high water-absorbing performance even for absorbing liquids with high salt concentrations, such as seawater. For example, Patent Document 1 discloses that water-stopping materials and the like are formed using amorphous water-absorbing resin particles having a specific volume average particle size and coefficient of variation, and including copolymer particles of an acrylic acid monomer and a monomer having sulfonic acid. By using such a water-absorbing resin as a water-stopping material, the water-absorbing performance and salt resistance of the water-stopping material for salt water and the like are improved. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-179382 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the water-absorbing resins used in conventional water-stopping materials do not have sufficient absorption performance for salt water, and therefore it is sometimes difficult to apply them as water-stopping materials for cables used in coastal areas, seawater, etc. Specifically, conventional water-absorbing resins have insufficient swelling performance (e.g., water absorption amount and water absorption speed) in salt water, and therefore have a low effect of stopping seawater, and therefore there is room for improvement in applying them as water-stopping materials for cables and the like that require water-stopping from seawater in coastal areas, etc.
[0007] The present invention has been made in view of the above, and provides a method for producing a water-absorbing material having excellent water absorption performance for salt water. (That is, it has a high water absorption capacity for salt water and a high water absorption speed.) An object of the present invention is to provide a water-absorbent resin, a water-stopping material including the water-absorbent resin, and a method for producing the water-absorbent resin. [Means for solving the problem]
[0008] As a result of intensive research to achieve the above-mentioned object, the present inventors have found that the water-stopping effect is significantly affected by the degree to which the water-absorbent resin swells in a short period of time (particularly one minute) after it starts to absorb saline solution, and further found that the above-mentioned object can be achieved by adjusting the swelling height in saline solution one minute after the start of water absorption, measured by a predetermined measurement method, to a specific range, and have thus completed the present invention.
[0009] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 A water-absorbing resin comprising partially neutralized polyacrylic acid, The polyacrylic acid has a crosslinked structure, A water-absorbent resin having a swelling height of 3.5 mm / 0.5 g or more in 3.3 mass % saline solution measured under the following measurement conditions. (Saline swelling height measurement conditions) 0.5 g of water-absorbent resin particles are scattered in a concave circular cup having a height of 30 mm and an inner diameter of 80.5 mm, a nonwoven fabric is laid on top of the particles, a convex circular cylinder having an outer diameter of 80 mm is placed on the nonwoven fabric, and 55 g of 3.3 mass % saline solution at 20° C. is poured into the concave circular cup. One minute after the water-absorbent resin particles start to absorb water, the distance by which the water-absorbent resin particles swell and push up the convex circular cylinder is measured, and this measured value is regarded as the saline swelling height of the water-absorbent resin. Section 2 Item 1. A water-stopping material comprising the water-absorbent resin according to item 1. Section 3 A step 1 of obtaining a partially neutralized polyacrylic acid by performing reverse phase suspension polymerization of a monomer component containing acrylic acid and a salt thereof and then drying the polymer; Step 2 of mixing the polyacrylic acid with a post-crosslinking agent to post-crosslink the polyacrylic acid; Including, A method for producing a water-absorbing resin, wherein in the step 1, the polyacrylic acid is dried so that the water content thereof becomes 10 to 30 mass %, and in the step 2, an amount of a post-crosslinking agent used is 0.20 millimol or more per mole of the total amount of the monomer components. Effect of the Invention
[0010] The water-absorbent resin according to the present invention has excellent water-absorbing performance for saline solution. Specifically, the water-absorbent resin of the present invention has a high water-absorption capacity for saline solution and also has a high water-absorption speed. Moreover, according to the method for producing a water-absorbent resin of the present invention, a water-absorbent resin having excellent water-absorbing performance for saline solution can be easily produced. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic explanatory diagram of a measuring device used for measuring the swelling height of a water-absorbent resin according to the present invention in a 3.3 mass % saline solution (swelling height in saline solution). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described in detail. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range can be arbitrarily combined with the upper limit or lower limit of another numerical range. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in an example or a value that can be unambiguously derived from an example. In addition, in this specification, a numerical value connected with "~" means a numerical range that includes the numerical values before and after "~" as the lower limit and upper limit.
[0013] 1.Water absorbent resin The water-absorbent resin of the present invention contains partially neutralized polyacrylic acid, the polyacrylic acid having a crosslinked structure, and a swelling height in 3.3% by mass saline solution measured under the following measurement conditions of 3.5 mm / 0.5 g or more. (Saline swelling height measurement conditions) 0.5 g of water-absorbent resin particles are scattered in a concave circular cup having a height of 30 mm and an inner diameter of 80.5 mm, a nonwoven fabric is laid on top of the particles, a convex circular cylinder having an outer diameter of 80 mm is placed on the nonwoven fabric, and 55 g of 3.3 mass % saline solution at 20° C. is poured into the concave circular cup. One minute after the water-absorbent resin particles start to absorb water, the distance by which the water-absorbent resin particles swell and push up the convex circular cylinder is measured, and this measured value is regarded as the saline swelling height of the water-absorbent resin. In the present invention, more detailed conditions for measuring the swelling height of a water-absorbent resin in saline solution are in accordance with the method described in [Method for measuring swelling height of a water-absorbent resin in saline solution] in the Examples section below.
[0014] The water-absorbent resin of the present invention has a swelling height (swelling height in saline) of 3.5 mm / 0.5 g or more in 3.3 mass % saline solution, and therefore has excellent water-absorption performance in saline solution. Specifically, the water-absorbent resin of the present invention has a high water-absorption amount in saline solution and also has a high water-absorption speed. In the following description, the swelling height in 3.3 mass % saline solution measured under the above measurement conditions is abbreviated to "saline swelling height H."
[0015] The saline swelling height H of the water-absorbent resin of the present invention (hereinafter simply referred to as "water-absorbent resin") is preferably 3.7 mm / 0.5 g or more, more preferably 3.9 mm / 0.5 g or more, even more preferably 4.0 mm / 0.5 g or more, and particularly preferably 4.1 mm / 0.5 g or more. The saline swelling height H can be 10.0 mm / 0.5 g or less, 8.0 mm / 0.5 g or less, 6.0 mm / 0.5 g or less, or 5.0 mm / 0.5 g or less.
[0016] The method for adjusting the saline swelling height H of the water absorbent resin is not particularly limited, and various methods can be mentioned. For example, the swelling speed height H of the water absorbent resin can be adjusted by controlling the degree of crosslinking of the water absorbent resin. In addition, as described later, in the production of the water absorbent resin, the saline swelling height H can be adjusted to a desired range by appropriately selecting the water content of the partially neutralized polyacrylic acid before post-crosslinking after obtaining the partially neutralized polyacrylic acid by reversed-phase suspension polymerization, the amount of the post-crosslinking agent used, the type of surfactant (emulsifier) used in reversed-phase suspension polymerization, the shape of the water absorbent resin, and other means.
[0017] The value of the water absorption amount of the water absorbent resin for the saline solution is not particularly limited. For example, the water absorption amount of the water absorbent resin for the saline solution is preferably 40 g / g or more, more preferably 42 g / g or more, even more preferably 45 g / g or more, and particularly preferably 47 g / g or more. In this specification, the water absorption amount of the water absorbent resin for the saline solution is measured according to the method described in [Method for measuring salt water absorption amount of water absorbent resin particles] in the Examples section described later.
[0018] The value of the water absorption rate of the water absorbent resin for the salt water is not particularly limited. For example, the water absorption amount of the water absorbent resin for the salt water is preferably 50 seconds or less, more preferably 30 seconds or less, further preferably 10 seconds or less, and particularly preferably 7 seconds or less. In this specification, the water absorption rate of the water absorbent resin for the salt water is measured according to the method described in [Method for measuring salt water absorption rate of water absorbent resin particles] in the Examples section described later.
[0019] The water-absorbing resin contains partially neutralized polyacrylic acid, and the partially neutralized polyacrylic acid may have various compositions and structures, etc., so long as it has a crosslinked structure. Such partially neutralized polyacrylic acid can be easily produced, for example, by employing reversed-phase suspension polymerization, which will be described later.
[0020] Partially neutralized polyacrylic acid has a structure in which a part of the acrylic acid units constituting the polyacrylic acid is neutralized. In the partially neutralized polyacrylic acid, the carboxyl group of the acrylic acid unit is neutralized to form a salt. Hereinafter, in this specification, the "partially neutralized polyacrylic acid" may be referred to as "polymer A".
[0021] In the polymer A, the type of salt is not particularly limited, and examples thereof include alkali metal salts, ammonium salts, etc. Examples of the alkali metal salts include sodium salts, potassium salts, etc. In particular, it is preferable that the polymer A contains a sodium salt.
[0022] In neutralizing acrylic acid, the degree of neutralization is not particularly limited. For example, from the viewpoint that the obtained water absorbent resin is likely to have a desired saline swelling height H, the amount of the acrylic acid salt is usually preferably 10 to 100 mol %, more preferably 30 to 80 mol %, based on the total number of moles of all monomer components constituting the polymer A.
[0023] Polymer A may contain other monomer units in addition to acrylic acid units and acrylate salts, so long as the effects of the present invention are not impaired. When polymer A contains other monomer units, the content ratio of such units is 5 mol % or less, preferably 3 mol % or less, more preferably 1 mol % or less, even more preferably 0.5 mol % or less, and particularly preferably 0.1 mol % or less, based on the total monomer components constituting polymer A. However, polymer A is preferably formed only from acrylic acid units and acrylate salt units.
[0024] The polymer A can have a structure crosslinked by a post-crosslinking agent described later. When the polymer A has a structure crosslinked by a post-crosslinking agent, the crosslink density in the vicinity of the surface of the water-absorbent resin is increased. The polymer A can have a structure crosslinked by a post-crosslinking agent and a structure crosslinked by an internal crosslinking agent described later, and can have a structure crosslinked by an intermediate crosslinking agent instead of or in addition to the structure crosslinked by the internal crosslinking agent. Examples of the internal crosslinking agent and the intermediate crosslinking agent will be described in detail in the section "2. Method for producing water-absorbent resin" below.
[0025] In this specification, the crosslinking agent used for crosslinking inside the polymer A is called the internal crosslinking agent. In addition, the crosslinking agent used after the particles of the polymer A (partially neutralized polyacrylic acid particles) are formed, for example, to increase the crosslinking density near the surface of the particles, is called the "post-crosslinking agent". Furthermore, the crosslinking agent used after the particles are obtained by polymerization and before drying to further impart crosslinking to the inside of the particles is called the intermediate crosslinking agent. Examples of the internal crosslinking agent and the intermediate crosslinking agent will be described in detail in the section "2. Manufacturing method of water-absorbent resin" below.
[0026] The post-crosslinking agent may be a compound having two or more reactive functional groups. The type of the post-crosslinking agent is not particularly limited, and may be a wide variety of crosslinking agents used for producing water-absorbent resins. Specific examples of the post-crosslinking agent include polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, trimethylolpropane, glycerin, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerin; polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether; epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, and the like. Examples of the epoxy compounds include haloepoxy compounds such as diisocyanate, isocyanate compounds such as 2,4-tolylene diisocyanate and hexamethylene diisocyanate; oxetane compounds such as 3-methyl-3-oxetanemethanol, 3-ethyl-3-oxetanemethanol, 3-butyl-3-oxetanemethanol, 3-methyl-3-oxetaneethanol, 3-ethyl-3-oxetaneethanol and 3-butyl-3-oxetaneethanol; oxazoline compounds such as 1,2-ethylenebisoxazoline; carbonate compounds such as ethylene carbonate; and hydroxyalkylamide compounds such as bis[N,N-di(β-hydroxyethyl)]adipamide. Among these, polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)ethylene glycol triglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, (poly)propylene glycol polyglycidyl ether, (poly)glycerol polyglycidyl ether, etc. are particularly preferred. These post-crosslinking agents may be used alone or in combination of two or more kinds.
[0027] The content of the post-crosslinking agent is not particularly limited as long as the saline swelling height H of the obtained water absorbent resin is adjusted to a desired range. For example, the lower limit of the content of the post-crosslinking agent is preferably 0.20 mmol, more preferably 0.25 mmol, even more preferably 0.30 mmol, and particularly preferably 0.35 mmol, relative to 1 mol of the total amount of all monomer components contained in the polymer A. The lower limit of the content of the post-crosslinking agent is preferably 10 mmol, more preferably 5 mmol, even more preferably 2 mmol, and particularly preferably 1 mmol, relative to 1 mol of the total amount of all monomer components contained in the polymer A.
[0028] The water-absorbent resin may contain other additives, in addition to the polymer A, so long as the effects of the present invention are not impaired. When the water-absorbent resin contains other additives, the content ratio of the other additives is 5% by mass or less, preferably 3% by mass or less, and more preferably 2% by mass or less, based on the total amount of the water-absorbent resin.
[0029] The water-absorbent resin may contain a chelating agent as necessary, which may improve the water-absorbent resin's ability to absorb saline.
[0030] The type of chelating agent is not particularly limited, and for example, a wide variety of known metal chelating agents can be used. The chelating agent preferably has 5 or more ligands. The upper limit of the number of ligands that the chelating agent has can be, for example, 12, 11, or 10.
[0031] Specific examples of the chelating agent include ethylenediaminetetraacetic acid, nitrilotriacetic acid, hydroxyethylenediaminetriacetic acid, diethylenetriaminepentaacetic acid, dihydroxyethylglycine, diethylenetriaminepentamethylenephosphonic acid, and salts thereof. When the chelating agent is in the form of a salt, the type of salt is not particularly limited, and examples thereof include alkali metal salts such as sodium and potassium, alkaline earth metal salts such as magnesium and calcium, organic amine salts, and ammonium salts. In the chelating agent, all or a part of the ligand can form a salt. Only one type of chelating agent can be used, or two or more types can be used in combination.
[0032] Of these, the chelating agent preferably used is diethylenetriaminepentaacetic acid and its salts, or diethylenetriaminepentamethylenephosphonic acid and its salts.
[0033] When the water-absorbent resin contains a chelating agent, the content of the chelating agent is not particularly limited. For example, the content of the chelating agent relative to 100 parts by mass of the water-absorbent resin is preferably 0.6 to 2.0 parts by mass, and more preferably 0.8 to 1.5 parts by mass.
[0034] When the water absorbent resin contains a chelating agent, the method of incorporating the chelating agent in the water absorbent resin is not particularly limited. A specific method for incorporating the chelating agent in the water absorbent resin will be described in detail in the section "2. Manufacturing method of water absorbent resin" below.
[0035] The shape of the water absorbent resin of the present invention may be various shapes, for example, spherical, pulverized, granular, oval, scaly, rod-like, lump-like, etc. In particular, the shape of the water absorbent resin is preferably granular, for example, a shape having an uneven surface such as a cauliflower-like shape, in that the water absorption performance for saline is easily improved.
[0036] The water-absorbing resin of the present invention is suitable for various applications because of its excellent water-absorbing performance against saline solution, and can be widely applied to various fields, such as industrial materials such as water-stopping materials and dew-preventing agents, sanitary materials such as paper diapers and sanitary products, agricultural and horticultural materials such as water-retaining agents and soil conditioners, etc. In particular, the water-absorbing resin has excellent water-absorbing performance against saline solution, and is therefore suitable for use as a water-stopping material for power cables and communication cables that require water-stopping against seawater in coastal areas.
[0037] In particular, when the water-absorbing resin is used in, for example, a water-stopping tape, since the water-absorbing resin has excellent water-absorbing performance against salt water, even if the tape is thinner than before, it can provide an excellent water-stopping effect.
[0038] The method for producing the water absorbent resin is not particularly limited, and for example, a wide variety of methods for producing water absorbent resins that have been conventionally employed can be employed, including reversed-phase suspension polymerization, aqueous solution polymerization, emulsion polymerization, etc. In particular, it is preferable to employ the reversed-phase suspension polymerization method, in that it is easy to adjust the saline swelling height H of the water absorbent resin to a desired range, and among these, it is preferable to employ a production method including steps 1 and 2 described below.
[0039] 2. Manufacturing method of water-absorbent resin The method for producing a water-absorbent resin of the present invention includes the following steps 1 and 2. Step 1: A step of obtaining partially neutralized polyacrylic acid by inverse suspension polymerization of monomer components containing acrylic acid and its salts, followed by drying. Step 2: A step of mixing the polyacrylic acid with a post-crosslinking agent to post-crosslink the polyacrylic acid. In particular, in the production method of the present invention, in the step 1, the polyacrylic acid is dried so that the water content is 10 to 30 mass %, and in the step 2, the amount of the post-crosslinking agent used is 0.20 mmol or more per mol of the total amount of the monomer components.
[0040] (Process 1) In step 1, a partially neutralized polyacrylic acid is obtained by reversed-phase suspension polymerization of a monomer component containing acrylic acid and its salt, and then the partially neutralized polyacrylic acid is dried. The reversed-phase suspension polymerization referred to here is, for example, a method of suspending a monomer component poorly soluble in a dispersion medium in the presence of a dispersion stabilizer, and polymerizing the monomer component. In the production method of the present invention, the monomer component poorly soluble in the dispersion medium contains acrylic acid and its salt. In this specification, the "monomer component containing acrylic acid and a salt thereof" used in step 1 is referred to as "monomer component A."
[0041] In step 1, the method for preparing the monomer component A is not particularly limited. For example, acrylic acid is mixed with a neutralizing agent to convert a part of the acrylic acid into an acrylate salt, thereby preparing the monomer component A. The acrylic acid can be obtained by a known production method, or can be obtained from a commercial product, etc.
[0042] As the neutralizing agent, for example, a wide variety of known alkaline neutralizing agents can be used, and specific examples include alkali metal salts such as sodium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium hydroxide, and potassium carbonate; ammonia, etc. The neutralizing agent can be used in the form of an aqueous solution to simplify the neutralization operation. The neutralizing agent may be used alone or in combination of two or more kinds.
[0043] In neutralizing acrylic acid, the degree of neutralization is not particularly limited. For example, from the viewpoint that the obtained water absorbent resin is likely to have a desired saline swelling height H, the content ratio of the acrylic acid salt is usually preferably 10 to 100 mol%, more preferably 30 to 80 mol%, based on the total number of moles of all monomer components constituting the polymer A.
[0044] The conditions for neutralizing acrylic acid are not particularly limited, and any known neutralization conditions can be widely adopted. For example, a method of dropping an aqueous solution of a neutralizing agent into an aqueous solution of acrylic acid can be mentioned.
[0045] In step 1, the monomer component A may contain other monomers other than acrylic acid and its salts, so long as the effects of the present invention are not impaired. When the monomer component A contains other monomers, the content of the other monomers is 5 mol % or less, preferably 3 mol % or less, more preferably 1 mol % or less, further preferably 0.5 mol % or less, and particularly preferably 0.1 mol % or less, based on the total monomers in the monomer component A. However, since the saline swelling height is likely to be 3.5 mm / 0.5 g or more, it is preferable that the monomer component A is composed only of acrylic acid and an acrylic acid salt.
[0046] The monomer component A containing acrylic acid and its salt may be made into an aqueous solution in order to increase the dispersion efficiency in a hydrocarbon dispersion medium when performing reverse phase suspension polymerization. The concentration of the monomer in such an aqueous solution is not particularly limited, but is usually 20% by mass or more and saturation concentration or less, preferably 25 to 90% by mass, and more preferably 30 to 85% by mass.
[0047] A hydrocarbon dispersion medium can be used as the dispersion medium used in reversed-phase suspension polymerization. Examples of the hydrocarbon dispersion medium include aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, and ligroin; alicyclic hydrocarbons such as cyclopentane, methylcyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbons such as benzene, toluene, and xylene. Among these dispersion media, n-hexane, n-heptane, and cyclohexane are preferably used because they are industrially easily available, have stable quality, and are inexpensive. These dispersion media may be used alone or in combination of two or more. Examples of the dispersion medium that can be used include Exxsol Heptane (manufactured by ExxonMobil: hydrocarbons of heptane and its isomers) and Nappar6 (manufactured by ExxonMobil: hydrocarbons of cyclohexane and its isomers), which are known as mixed solvents.
[0048] In the reversed-phase suspension polymerization, a thickener can be used as necessary. Examples of the thickener that can be used include hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, polyacrylic acid, polyacrylic acid (partially) neutralized product, polyethylene glycol, polyacrylamide, polyethyleneimine, dextrin, sodium alginate, polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene oxide.
[0049] As the dispersion stabilizer used in the reversed-phase suspension polymerization, a surfactant may be used, and examples thereof include sucrose fatty acid esters, polyglycerin fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerin fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkylaryl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl gluconamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, phosphoric acid esters of polyoxyethylene alkyl ethers, and phosphoric acid esters of polyoxyethylene alkyl allyl ethers. Among these, from the viewpoint of dispersion stability of the monomer, sorbitan fatty acid esters, polyglycerin fatty acid esters, sucrose fatty acid esters, and the like are preferred. These surfactants may be used alone or in combination of two or more. Among the sorbitan fatty acid esters, particular mention may be made of sorbitan monolaurate.
[0050] When the dispersion stabilizer used in the reversed-phase suspension polymerization is the above-mentioned surfactant, from the viewpoint of easily adjusting the saline solution swelling height H of the water absorbent resin to a desired range, the HLB value of the surfactant is preferably 3.5 to 12, more preferably 8 to 12, and particularly preferably 8.5 to 10.5.
[0051] The amount of the surfactant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, per 100 parts by mass of the first-stage water-soluble ethylenically unsaturated monomer, in order to maintain a good dispersion state of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium and to obtain a dispersion effect commensurate with the amount used.
[0052] As a dispersion stabilizer, a polymeric dispersant may be used in combination with the surfactant. Examples of polymeric dispersants that can be used include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified EPDM (ethylene-propylene-diene-terpolymer), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, and ethylhydroxyethyl cellulose. Among these, from the viewpoint of dispersion stability of the monomer, preferred are maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, etc. These polymeric dispersants may be used alone or in combination of two or more kinds.
[0053] The amount of the polymeric dispersant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, per 100 parts by mass of the total amount of the first stage monomer component A described below, in order to maintain a good dispersion state of the monomer component A containing acrylic acid and its salt in the hydrocarbon dispersion medium and to obtain a dispersion effect commensurate with the amount used.
[0054] In the reversed-phase suspension polymerization in the first step, for example, a wide variety of known polymerization initiators can be used. Examples of the radical polymerization initiator include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-t-butyl peroxide, t-butyl cumyl peroxide, and hydrogen peroxide; and azo compounds such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(N-phenylamidino)propane] dihydrochloride, 2,2'-azobis[2-(N-allylamidino)propane] dihydrochloride, and 4,4'-azobis(4-cyanovaleric acid). The radical polymerization initiator can also be used in combination with a reducing agent such as sodium sulfite, sodium hydrogen sulfite, ferrous sulfate, or L-ascorbic acid to form a redox polymerization initiator.
[0055] The lower limit of the amount of radical polymerization initiator used in the reversed-phase suspension polymerization is preferably 0.01 mmol, more preferably 0.05 mmol, per mole of the total amount of monomer component A used, from the viewpoint of polymerization stability. The upper limit of the radical polymerization initiator is preferably 20 mmol, more preferably 10 mmol, per mole of the total amount of monomer component A used, from the viewpoint of polymerization stability. By using the radical polymerization initiator within this range, the production of the water-absorbing resin becomes easier.
[0056] In the reversed-phase suspension polymerization, a chain transfer agent can be used as necessary. Examples of the chain transfer agent include hypophosphites, thiols, thiolic acids, secondary alcohols, and amines.
[0057] In the reversed-phase suspension polymerization, an internal crosslinking agent can be used as necessary. This allows the polymer (partially neutralized polyacrylic acid) obtained by the reversed-phase suspension polymerization to have a structure in which the inside is crosslinked with the internal crosslinking agent. The internal crosslinking agent is added to the monomer component A containing, for example, acrylic acid and its salt. The internal cross-linking agent may be a compound having two or more polymerizable unsaturated groups. A specific example of the internal cross-linking agent is (poly)ethylene glycol (for example, in this specification, "polyethylene glycol" and "ethylene glycol" are collectively referred to as "(poly)ethylene glycol"). the same applies below], di- or tri(meth)acrylic acid esters of polyols such as (poly)propylene glycol, trimethylolpropane, glycerin polyoxyethylene glycol, polyoxypropylene glycol, and (poly)glycerin; unsaturated polyesters obtained by reacting the above-mentioned polyols with unsaturated acids such as maleic acid and fumaric acid; bisacrylamides such as N,N'-methylenebis(meth)acrylamide; di- or tri(meth)acrylic acid esters obtained by reacting polyepoxides with (meth)acrylic acid; di(meth)acrylic acid carbamyl esters obtained by reacting polyisocyanates such as tolylene diisocyanate and hexamethylene diisocyanate with hydroxyethyl (meth)acrylate; allylated starch; allylated cellulose; diallyl phthalate; N,N',N''-triallyl isocyanurate; and divinylbenzene.
[0058] In addition, examples of the internal crosslinking agent include compounds having two or more polymerizable unsaturated groups, such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerin diglycidyl ether, and other glycidyl group-containing compounds; (poly)ethylene glycol, (poly)propylene glycol, (poly)glycerin, pentaerythritol, ethylenediamine, polyethyleneimine, and glycidyl (meth)acrylate. Two or more of these internal crosslinking agents may be used in combination. Among these, from the viewpoint of excellent reactivity at low temperatures, (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerin diglycidyl ether and N,N'-methylenebisacrylamide are preferred.
[0059] When an internal crosslinking agent is used, its amount is not particularly limited, and from the viewpoint of ease of production of the water absorbent resin, the lower limit of the amount of the internal crosslinking agent used is preferably 0.0001 mmol, more preferably 0.0005 mmol, even more preferably 0.001 mmol, and particularly preferably 0.01 mmol, relative to 1 mol of the total amount of the monomer component A used. The upper limit of the amount of the internal crosslinking agent used is preferably 5 mmol, more preferably 0.5 mmol, and even more preferably 0.05 mmol, relative to 1 mol of the total amount of the monomer component A used. The water absorbent resin obtained through steps 1 and 2 has a crosslinked structure inside. The crosslinking density of the internal crosslinks can be appropriately adjusted according to the amount of the internal crosslinking agent used as necessary. In the production method of the present invention, it is also preferable not to use the internal crosslinking agent, since it is easy to adjust the saline swelling height H to a desired range.
[0060] In the reversed-phase suspension polymerization, the polymerization reaction temperature can be appropriately set depending on the type and amount of the radical polymerization initiator used, and can be, for example, 20 to 110° C., and preferably 40 to 90° C. The reaction time can be set, for example, in the range of 0.1 to 4 hours.
[0061] In step 1, the reversed-phase suspension polymerization can be carried out by, for example, adding an aqueous solution containing a monomer component (monomer component A) containing acrylic acid and its salt, a radical polymerization initiator, and an internal crosslinking agent used as required to a dispersion medium in which a surfactant is dissolved, to create a suspended state. The order in which the raw materials are added is not limited to this.
[0062] In the reversed-phase suspension polymerization, the monomer component A is polymerized to produce the partially neutralized polyacrylic acid (the polymer A). For example, in the reversed-phase suspension polymerization, a slurry in which the partially neutralized polyacrylic acid is dispersed is obtained. The polymer A obtained by the reversed-phase suspension polymerization is, for example, in a swollen gel state. Usually, the partially neutralized polyacrylic acid obtained by the reversed-phase suspension polymerization has a particle shape. It should be noted that the polymer A obtained by the reversed-phase suspension polymerization in step 1 is not post-crosslinked, just for the sake of caution.
[0063] The reversed-phase suspension polymerization may be carried out in one stage, or in two or more stages. When carrying out reversed-phase suspension polymerization in two or more stages, the first stage of the reversed-phase suspension polymerization is carried out by the above-mentioned method, and then the monomer component A is added to and mixed with the reaction mixture obtained in the first stage of the polymerization, and the second and subsequent stages of the reversed-phase suspension polymerization are carried out in the same manner as the first stage. In the reversed-phase suspension polymerization in each stage after the second stage, in addition to the monomer component A, a radical polymerization initiator and an internal crosslinking agent added as necessary are added within the range of the molar ratio of each component to the monomer component A described above, based on the amount of the water-soluble ethylenically unsaturated monomer added during the reversed-phase suspension polymerization in each stage after the second stage, and the reversed-phase suspension polymerization is carried out under the same conditions as the above-mentioned method.
[0064] In addition, when the reversed-phase suspension polymerization is carried out in multiple stages, it is preferable that the total amount of the polymerization initiator and the total amount of the internal crosslinking agent used as needed per mole of the total amount of the monomer component A used in the reversed-phase suspension polymerization are each within the above-mentioned range.
[0065] In step 1, after the reversed-phase suspension polymerization, a crosslinking agent may be added to the reaction mixture obtained by the reversed-phase suspension polymerization before the drying treatment described below, if necessary. The crosslinking agent used here is the intermediate crosslinking agent described above.
[0066] The type of intermediate crosslinking agent is not particularly limited, and for example, the same type of crosslinking agent as the internal crosslinking agent can be exemplified, and the intermediate crosslinking agent that can be preferably used is also the same as the internal crosslinking agent. When the intermediate crosslinking agent and the internal crosslinking agent are used, the type may be the same as or different from the internal crosslinking agent. The lower limit of the amount of intermediate crosslinking agent used is not particularly limited, and for example, it is preferably 0.0001 mmol, more preferably 0.0005 mmol, even more preferably 0.001 mmol, and particularly preferably 0.01 mmol, relative to 1 mol of the total amount of monomer component A used. The upper limit of the amount of intermediate crosslinking agent used is preferably 5 mmol, more preferably 0.5 mmol, and even more preferably 0.05 mmol, relative to 1 mol of the total amount of monomer component A used.
[0067] In step 1, after polymer A (partially neutralized polyacrylic acid) is produced by the reversed-phase suspension polymerization, a drying treatment is carried out. The drying treatment is a step of removing water from the polymer obtained by the reversed-phase suspension polymerization by applying external energy such as heat.
[0068] In step 1, the polymer A is dried so that the water content is 10 to 30% by mass. By adjusting the water content to the above range by the drying treatment in step 1, the crosslinking density by post-crosslinking performed in the subsequent step can be easily adjusted to an appropriate range, so that the saline swelling height H of the obtained water absorbent resin can be adjusted to a desired range. The lower limit of the water content of the polymer A obtained by the drying treatment is preferably 11% by mass, more preferably 12% by mass, even more preferably 13% by mass, even more preferably 14% by mass, and particularly preferably 15% by mass. The upper limit of the water content of the polymer A obtained by the drying treatment is preferably 29% by mass, more preferably 28% by mass, even more preferably 27% by mass, and particularly preferably 26% by mass. The water content here means the water content (% by mass) based on the total mass of polymer A (partially neutralized polyacrylic acid containing water) obtained after drying. Specifically, the water content of polymer A means the percentage of the mass of water remaining in the reaction system after the drying treatment relative to the total mass of the monomer components subjected to the polymerization reaction, and the water subjected to the polymerization reaction and the water generated in the neutralization reaction, and is calculated by the following formula (1). In the following formula (1), the mass of water remaining in the reaction system is calculated by subtracting the mass of water removed by the drying treatment from the mass of water subjected to the polymerization reaction and the mass of water generated in the neutralization reaction. Moisture content = {mass of water remaining in the reaction system / (mass of monomer components used in the polymerization reaction + mass of water used in the polymerization reaction + mass of water produced in the neutralization reaction)} × 100 (1)
[0069] The method of drying treatment for adjusting the water content as described above is not particularly limited. For example, the drying treatment can be performed by azeotropic distillation of the polymer A obtained by reversed-phase suspension polymerization while it is dispersed in a dispersion medium. This drying treatment may be performed under normal pressure or reduced pressure, and may be performed under a stream of nitrogen or the like to increase the drying efficiency. When the drying treatment is performed under normal pressure, the drying temperature is preferably 70 to 250°C, more preferably 80 to 180°C, further preferably 80 to 140°C, and particularly preferably 90 to 130°C. When the drying treatment is performed under reduced pressure, the drying temperature is preferably 40 to 160°C, more preferably 50 to 120°C. The water content of the polymer A (partially neutralized polyacrylic acid) can be adjusted by appropriately selecting the drying temperature and drying time (i.e., the temperature and time of azeotropic distillation). By the above drying treatment, a dispersion in which the polymer A with a water content adjusted to a desired range is dispersed in the dispersion medium can be obtained.
[0070] (Process 2) Step 2 is a step for post-crosslinking the polyacrylic acid by mixing the partially neutralized polyacrylic acid (polymer A obtained in step 1) obtained in step 1 and having a water content adjusted to a predetermined range with a post-crosslinking agent.
[0071] The type of post-crosslinking agent used in step 2 is not particularly limited, and examples thereof include the same types as the post-crosslinking agents described in the above section "1. Water-absorbent resin", and the same applies to post-crosslinking agents that can be preferably used. As a method of post-crosslinking, for example, a post-crosslinking agent and a solvent are mixed to prepare a treatment liquid containing the post-crosslinking agent, and this treatment liquid is brought into contact with the partially neutralized polyacrylic acid, thereby treating the partially neutralized polyacrylic acid with the post-crosslinking agent.
[0072] The solvent for preparing the treatment liquid containing the post-crosslinking agent is not particularly limited, and for example, a hydrophilic organic solvent having excellent solubility of the post-crosslinking agent can be used. Examples of the solvent include water, lower alcohols such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and propylene glycol; ketones such as acetone and methyl ethyl ketone; ethers such as diethyl ether, dioxane, and tetrahydrofuran; amides such as N,N-dimethylformamide; and sulfoxides such as dimethyl sulfoxide. These hydrophilic organic solvents may be used alone, or two or more of them may be used in combination, or they may be used as a mixed solvent with water.
[0073] The treatment liquid can be prepared, for example, by dissolving a post-crosslinking agent in a solvent. The mixing ratio of the post-crosslinking agent to the solvent is not particularly limited, and for example, the post-crosslinking agent can be 0.1 to 10 parts by mass per 100 parts by mass of the solvent. The method of mixing the polymer A obtained in step 1 with the treatment liquid is not particularly limited, and for example, a method of adding the treatment liquid to the partially neutralized polyacrylic acid contained in a container can be adopted. The partially neutralized polyacrylic acid contained in the container contains the dispersion medium used in the reversed-phase suspension polymerization.
[0074] The amount of the post-crosslinking agent used is not particularly limited as long as the saline swelling height H of the obtained water absorbent resin is adjusted to a desired range. For example, the lower limit of the amount of the post-crosslinking agent used is preferably 0.20 mmol, more preferably 0.25 mmol, even more preferably 0.30 mmol, and particularly preferably 0.35 mmol, relative to 1 mole of the total amount of the monomer component A. The upper limit of the amount of the post-crosslinking agent used is preferably 10 mmol, more preferably 5 mmol, even more preferably 2 mmol, even more preferably 1 mmol, and particularly preferably 0.8 mmol, relative to 1 mole of the total amount of the monomer component A.
[0075] The reaction temperature in the post-crosslinking (i.e., the temperature at which the partially neutralized polyacrylic acid is treated with a post-crosslinking agent) is preferably 50 to 250° C., more preferably 60 to 180° C., and even more preferably 60 to 140° C. The reaction time of the post-crosslinking (i.e., the time at which the partially neutralized polyacrylic acid is treated with a post-crosslinking agent at the reaction temperature) cannot be determined in general because it varies depending on the reaction temperature, the type and amount of the post-crosslinking agent used, etc., but is usually 1 to 300 minutes, and preferably 5 to 200 minutes.
[0076] The post-crosslinking can obtain a polymer A having a post-crosslinked structure. In this post-crosslinking, for example, the surface vicinity of the polyacrylic acid particles can selectively have a crosslinked structure. In step 2, after the post-crosslinking, a heating treatment can be performed as necessary to evaporate the remaining dispersion medium. In this case, for example, after the post-crosslinking treatment, the heating treatment can be performed after cooling once, or the heating treatment can be performed by further increasing the temperature after the post-crosslinking treatment.
[0077] The manufacturing method of the present invention may further include a step of adding a chelating agent (hereinafter, abbreviated as "chelating agent adding step") in addition to step 1 and step 2. The chelating agent adding step is a step for incorporating a chelating agent into the water absorbent resin. Examples of the type of chelating agent include the same types as the chelating agents described in the above section "1. Water absorbent resin". The chelating agent addition step can be carried out, for example, before the drying treatment in step 1, or the chelating agent addition step can be carried out during the reversed-phase suspension polymerization. When the chelating agent addition step is carried out during the reversed-phase suspension polymerization, the chelating agent may be added to the vessel in which the polymerization reaction is carried out before the polymerization reaction proceeds, or may be added to the vessel in which the polymerization reaction is carried out during the polymerization reaction. The chelating agent addition step can also be carried out after the post-crosslinking step in step 2. The chelating agent addition step is preferably carried out after the end of the reversed-phase suspension polymerization in step 1, and more preferably before the drying treatment.
[0078] When the chelating agent is added, the chelating agent can be added in a state of solution dissolved in a solvent such as water, or can be added in a solid state without using a solvent. When the chelating agent is added, the partially neutralized polyacrylic acid can be in a state of being dispersed in a dispersion medium, or in a state of powder or the like from which the dispersion medium has been removed. When the polymer is in a powder state, the so-called dry blending method can be adopted in the chelating agent addition step.
[0079] In the chelating agent addition step, the amount of the chelating agent used is not particularly limited. For example, from the viewpoint that the swelling speed height H is easily within the desired range, the lower limit of the amount of the chelating agent used is preferably 0.25 mmol, more preferably 0.3 mmol, even more preferably 0.4 mmol, and particularly preferably 0.45 mmol, per mol of the total amount of the monomer component A. The upper limit of the amount of the chelating agent used is preferably 10 mmol, more preferably 5 mmol, and even more preferably 3 mmol, per mol of the total amount of the monomer component A.
[0080] When the production method of the present invention includes the step of adding a chelating agent, the obtained water-absorbent resin contains a chelating agent. The manufacturing method of the present invention may include a step of blending other additives in each step of step 1 and step 2, and further in the step of adding the chelating agent as required, or separately from these steps. The other additives can impart various properties to the obtained water absorbent resin according to its purpose. Examples of such additives include various additives that have been conventionally added to water absorbent resins, such as inorganic powders, surfactants, oxidizing agents, reducing agents, radical chain inhibitors, antioxidants, antibacterial agents, and deodorants.
[0081] 3.Water-stopping materials The water-stopping material of the present invention is not particularly limited in its configuration as long as it includes a water-absorbent resin, and may have, for example, the same configuration as known water-stopping materials. The water-stopping material may be formed from a water-absorbent resin alone. Alternatively, the water-stopping material may be formed by molding a mixture of the water-absorbent resin and rubber and / or a thermoplastic resin or the like. The water-stopping material may also be formed by holding the water-absorbent resin on a nonwoven fabric or paper.
[0082] The water-stopping material of the present invention can be applied to various applications, and can be used in various cables, such as communication cables such as optical cables and metal cables, and power cables. In particular, the water-stopping material containing a water-absorbing resin has excellent water-absorbing performance against salt water, and can be suitably used in power cables that require water-stopping seawater in coastal areas, and optical fiber cables used underground and on the seabed. In addition, since the water-stopping material has excellent water-absorbing performance against salt water, when used as a water-stopping tape, for example, the desired water-stopping effect can be obtained even if the thickness is made thinner than before. EXAMPLES
[0083] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples. [Example 1] (Step 1: Inverse Phase Suspension Polymerization) A round-bottomed cylindrical separable flask (hereinafter referred to as round-bottomed flask) with an inner diameter of 110 mm and equipped with a reflux condenser, a dropping funnel, a nitrogen gas inlet tube, and a stirring blade (coated with a fluororesin) having two stages of four inclined paddle blades with a blade diameter of 50 mm was prepared. 485 mL of n-heptane was added to the round-bottomed flask as a petroleum-based hydrocarbon dispersion medium, and 1.10 g of sorbitan monolaurate (manufactured by NOF Corporation, trade name Nonion LP-20R; HLB 8.6) was added as a surfactant, and the temperature was raised to 50°C to prepare an n-heptane solution of the surfactant.
[0084] On the other hand, 92g (1.03 mol) of 80.5% by mass acrylic acid aqueous solution was added to a 300mL beaker as a water-soluble ethylenically unsaturated monomer aqueous solution. While cooling the acrylic acid aqueous solution with ice water, 147.7g of 20.9% by mass sodium hydroxide aqueous solution was dropped into the beaker to neutralize 75 mol% of the acrylic acid. Then, 0.10g (0.00037 mol) of potassium persulfate was added and dissolved as a radical polymerization initiator to prepare an aqueous solution.
[0085] Next, the entire amount of the aqueous liquid was added to the n-heptane solution of the surfactant in the round-bottom flask, and the inside of the round-bottom flask was replaced with nitrogen for 30 minutes while stirring at a stirrer speed of 700 rpm. After that, the round-bottom flask was immersed in a water bath at 70°C to raise the temperature inside the system, and the polymerization reaction was carried out for 1 hour to carry out reversed-phase suspension polymerization. A hydrous gel polymer was obtained in the round-bottom flask by this reversed-phase suspension polymerization.
[0086] (Step 1: Drying) Next, the round-bottom flask after the reversed-phase suspension polymerization was immersed in an oil bath at 125°C, and 126.64g of water was extracted from the system while refluxing n-heptane by azeotroping water and n-heptane, thereby performing a drying treatment, thereby obtaining a partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 19.5%. The water content was calculated based on the above formula (1).
[0087] (Step 2; Post-crosslinking) After that, 4.14g (0.48mmol) of 2% by mass ethylene glycol diglycidyl ether aqueous solution was added to the round-bottom flask as a post-crosslinking agent.Then, the round-bottom flask was heated to a treatment temperature of 83°C with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid.Then, the round-bottom flask was heated to 125°C, and n-heptane in the round-bottom flask was evaporated at 125°C to obtain 91.82g of granular water-absorbent resin particles.
[0088] [Example 2] Inverse phase suspension polymerization was carried out in the same manner as in Example 1. After this reverse phase suspension polymerization, the round bottom flask was immersed in an oil bath at 125°C, and 125.12g of water was extracted from the system while refluxing n-heptane by azeotroping water and n-heptane, thereby obtaining a partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 20.5%. After this, 5.52g (0.63 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether was added to the round bottom flask as a post-crosslinking agent. Next, the round bottom flask was heated to a treatment temperature of 83°C with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid (step 2). After that, the round bottom flask was heated to 125°C, and n-heptane in the round bottom flask was evaporated at 125°C to obtain 82.27g of granular water absorbent resin particles.
[0089] [Example 3] Inverse phase suspension polymerization was carried out in the same manner as in Example 1. After this inverse phase suspension polymerization, 0.41 g (0.047 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether was added to the round-bottom flask as an intermediate crosslinking agent before carrying out a drying treatment. Next, the round-bottom flask after the inverse phase suspension polymerization was immersed in an oil bath at 125°C, and azeotropic distillation of water and n-heptane was carried out, whereby 121.00 g of water was extracted from the system while refluxing n-heptane, thereby obtaining a partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 23.3%. After that, 4.14g (0.48mmol) of 2% by mass ethylene glycol diglycidyl ether aqueous solution was added to the round-bottom flask as a post-crosslinking agent.Then, the round-bottom flask was heated to a treatment temperature of 83°C with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid.Then, the round-bottom flask was heated to 125°C, and n-heptane in the round-bottom flask was evaporated at 125°C to obtain 82.12g of granular water-absorbing resin particles.
[0090] [Example 4] Inverse suspension polymerization was carried out in the same manner as in Example 1. After this inverse suspension polymerization, the round-bottom flask was immersed in an oil bath at 125°C to azeotrope water and n-heptane, and 129.65 g of water was extracted from the system while refluxing n-heptane, thereby obtaining a partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 18.0%. Thereafter, 2.10 g (1.9 mmol) of a 45% by mass aqueous solution of diethylenetriaminepentaacetic acid pentasodium salt was added to the round-bottom flask as a chelating agent before adding a post-crosslinking agent. Then, 4.14 g (0.48 mmol) of 2% by mass ethylene glycol diglycidyl ether aqueous solution was added to the round-bottom flask as a post-crosslinking agent. The round-bottom flask was then heated to a treatment temperature of 83° C. with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid. The round-bottom flask was then heated to 125° C., and n-heptane in the round-bottom flask was evaporated at 125° C. to obtain 89.40 g of granular water-absorbing resin particles.
[0091] [Comparative Example 1] Inverse phase suspension polymerization was carried out in the same manner as in Example 1. After this reverse phase suspension polymerization, the round bottom flask was immersed in an oil bath at 125°C, and 111.69g of water was extracted from the system while refluxing n-heptane by azeotroping water and n-heptane, thereby obtaining a partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 28.9%. After this, 2.76g (0.32 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether was added to the round bottom flask as a post-crosslinking agent. Next, the round bottom flask was heated to a treatment temperature of 83°C with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid (step 2). After that, the round bottom flask was heated to 125°C, and n-heptane in the round bottom flask was evaporated at 125°C to obtain 82.85g of granular water absorbent resin particles.
[0092] [Comparative Example 2] Inverse phase suspension polymerization was carried out in the same manner as in Example 1. After this reverse phase suspension polymerization, the round bottom flask was immersed in an oil bath at 125°C, and 122.46g of water was extracted from the system while refluxing n-heptane by azeotroping water and n-heptane, thereby obtaining a partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 22.3%. After this, 1.84g (0.21 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether was added to the round bottom flask as a post-crosslinking agent. Next, the round bottom flask was heated to a treatment temperature of 83°C with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid (step 2). After that, the round bottom flask was heated to 125°C, and n-heptane in the round bottom flask was evaporated at 125°C to obtain 83.33g of granular water absorbent resin particles.
[0093] [Comparative Example 3] Inverse suspension polymerization was carried out in the same manner as in Example 1. After this inverse suspension polymerization, the round-bottom flask was immersed in an oil bath at 125°C to azeotrope water and n-heptane, and 136.96 g of water was extracted from the system while refluxing n-heptane, thereby obtaining a partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 11.4%. Thereafter, 2.10 g (1.9 mmol) of a 45% by mass aqueous solution of diethylenetriaminepentaacetic acid pentasodium salt was added to the round-bottom flask as a chelating agent before adding a post-crosslinking agent. Then, 4.14 g (0.48 mmol) of 2% by mass ethylene glycol diglycidyl ether aqueous solution was added to the round-bottom flask as a post-crosslinking agent. The round-bottom flask was then heated to a treatment temperature of 83° C. with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid. The round-bottom flask was then heated to 125° C., and n-heptane in the round-bottom flask was evaporated at 125° C. to obtain 89.40 g of granular water-absorbing resin particles.
[0094] [Comparative Example 4] A round-bottomed cylindrical separable flask (hereinafter referred to as round-bottom flask) with an inner diameter of 110 mm and equipped with a reflux condenser, a dropping funnel, a nitrogen gas inlet tube, and a stirring blade with two stages of four inclined paddle blades with a blade diameter of 50 mm was prepared. 293 g of n-heptane was added to the round-bottom flask as a petroleum-based hydrocarbon dispersion medium, 0.74 g of sucrose stearate ester (Ryoto Sugar Ester S-370; HLB3, Mitsubishi Chemical Foods Corporation) as a surfactant, and 0.74 g of maleic anhydride-modified ethylene-propylene copolymer (Hiwax 1105A, Mitsui Chemicals, Inc.) as a polymer dispersant were added, and the temperature was raised to 80°C with stirring to dissolve the surfactant, and then the mixture was cooled to 50°C. On the other hand, 92g (1.03 mol) of 80.5% by mass acrylic acid aqueous solution was added to a 300mL beaker as a water-soluble ethylenically unsaturated monomer aqueous solution. While cooling the acrylic acid aqueous solution with ice water, 147.7g of 20.9% by mass sodium hydroxide aqueous solution was dropped into the beaker to neutralize 75 mol% of the acrylic acid. Then, 0.074g (0.27 mmol) of potassium persulfate as a radical polymerization initiator and 0.51g (0.058 mmol) of 2% by mass ethylene glycol diglycidyl ether aqueous solution as an internal crosslinking agent were added and dissolved to prepare a first-stage monomer aqueous solution. The entire amount of the first-stage monomer aqueous solution was added to the round-bottom flask, and the inside of the system was thoroughly replaced with nitrogen. The flask was then immersed in a 70°C water bath to raise the temperature, and the first-stage polymerization was carried out for 30 minutes to obtain a first-stage reaction mixture. Meanwhile, 128.8g (1.43 mol) of an 80.5% by mass acrylic acid aqueous solution was placed in another 300mL beaker, and while cooling from the outside, 160.9g of a 26.8% by mass sodium hydroxide aqueous solution was added dropwise to carry out 75 mol% neutralization. Then, 0.10g (0.37 mmol) of potassium persulfate as a radical polymerization initiator and 0.58g (0.067 mmol) of a 2% by mass ethylene glycol diglycidyl ether aqueous solution as an internal crosslinking agent were added and dissolved to prepare a second-stage monomer aqueous solution.
[0095] The reaction mixture of the first stage was cooled to 24°C, and the aqueous monomer solution of the second stage at the same temperature was added to the system and absorbed for 30 minutes. At the same time, the atmosphere in the system was sufficiently replaced with nitrogen. After that, the flask was again immersed in a water bath at 70°C to raise the temperature, and the second stage polymerization was carried out for 30 minutes. After the second polymerization step, the reaction mixture was heated in an oil bath at 125°C, and 269.48g of water was extracted from the system while refluxing n-heptane by azeotropic distillation of n-heptane and water, and a drying treatment was performed, thereby obtaining partially neutralized polyacrylic acid. The water content of the partially neutralized polyacrylic acid after this drying treatment was 16.0%. After this, 0.58g (0.53mmol) of a 45% by mass aqueous solution of diethylenetriaminepentaacetic acid·pentasodium salt was added as a chelating agent. Next, 4.42g (0.51mmol) of a 2% aqueous solution of ethylene glycol diglycidyl ether was added as a post-crosslinking agent, and then the reaction mixture was heated in an oil bath at 125°C, and n-heptane was evaporated and dried, obtaining 83.8g of a water-absorbent resin.
[0096] [Comparative Example 5] A round-bottomed cylindrical separable flask (hereinafter referred to as round-bottom flask) with an inner diameter of 110 mm and equipped with a reflux condenser, a dropping funnel, a nitrogen gas inlet tube, and a stirring blade with two stages of four inclined paddle blades with a blade diameter of 50 mm was prepared. 293 g of n-heptane was added to the round-bottom flask as a petroleum-based hydrocarbon dispersion medium, 0.74 g of sucrose stearate ester (Ryoto Sugar Ester S-370; HLB3, Mitsubishi Chemical Foods Corporation) as a surfactant, and 0.74 g of maleic anhydride-modified ethylene-propylene copolymer (Hiwax 1105A, Mitsui Chemicals, Inc.) as a polymer dispersant were added, and the temperature was raised to 80°C with stirring to dissolve the surfactant, and then the mixture was cooled to 50°C. On the other hand, 26.1g (0.29 mol) of 80.5% by mass acrylic acid aqueous solution was added to a 300mL beaker as a water-soluble ethylenically unsaturated monomer aqueous solution. While the acrylic acid aqueous solution was cooled with ice water, 41.9g of 20.9% by mass sodium hydroxide aqueous solution was dropped into the beaker to neutralize 75% by mole of the acrylic acid. Next, 75.1g (0.29 mol) of 80.5% by mass 2-acrylamido 2-methylpropanesulfonic acid (ATBS) aqueous solution was added to another 300mL beaker. While the 2-acrylamido 2-methylpropanesulfonic acid aqueous solution was cooled with ice water, 96.6g of 9.1% by mass sodium hydroxide aqueous solution was dropped into the beaker to neutralize 75% by mole of the 2-acrylamido 2-methylpropanesulfonic acid. Thereafter, the entire amount of the 75 mol % neutralized acrylic acid aqueous solution was added, and 0.052 g (0.19 mmol) of 2,2'-azobis(2-amidinopropane) dihydrochloride and 0.021 g (0.077 mmol) of potassium persulfate were added and dissolved as radical polymerization initiators, and 1.56 g (0.090 mmol) of a 1 mass % aqueous ethylene glycol diglycidyl ether solution as an internal crosslinking agent was added and dissolved to prepare an aqueous liquid.
[0097] Next, the entire amount of the aqueous liquid was added to the n-heptane solution of the surfactant in a round-bottom flask, and the inside of the round-bottom flask was replaced with nitrogen for 30 minutes while stirring at a stirrer speed of 160 rpm. After this, the round-bottom flask was immersed in a water bath at 70°C to raise the temperature inside the system, and a polymerization reaction was carried out for 30 minutes to carry out reversed-phase suspension polymerization. By this reversed-phase suspension polymerization, a hydrous gel-like polymer was obtained in the round-bottom flask. Next, the round-bottom flask after the reversed-phase suspension polymerization was immersed in an oil bath at 125°C to azeotrope water and n-heptane, and 120.58 g of water was extracted from the system while refluxing n-heptane, thereby carrying out a drying treatment, and thus a partially neutralized polyacrylic acid was obtained. The water content of the partially neutralized polyacrylic acid after this drying treatment was 23.5%. After that, 1.05g (0.30mmol) of 5% by mass ethylene glycol diglycidyl ether aqueous solution was added to the round-bottom flask as a post-crosslinking agent.Then, the round-bottom flask was heated to a treatment temperature of 80°C with the post-crosslinking agent, and the temperature was maintained for 2 hours to perform post-crosslinking of the partially neutralized polyacrylic acid.Then, the round-bottom flask was heated to 125°C, and n-heptane in the round-bottom flask was evaporated at 125°C to obtain 83.20g of granular water-absorbent resin particles.
[0098] [Method for measuring salt water absorption of water-absorbent resin particles] 500 g of 3.3% by mass saline was placed in a 500 mL beaker, and 2.0 g of water-absorbent resin particles were added thereto and stirred for 60 minutes. The mass Wa (g) of a JIS standard sieve with a mesh size of 75 μm was measured in advance, and the contents of the beaker were filtered using this. The sieve was tilted at an angle of about 30 degrees to the horizontal and left for 15 minutes to filter out excess water. The mass Wb (g) of the sieve containing the water-absorbing gel was measured, and the amount of water absorption was calculated using the following formula. Salt water absorption = (Wb-Wa) / 2.0
[0099] [Method for measuring the salt water absorption rate of water-absorbent resin particles] The water absorption rate was measured in a room adjusted to 25°C ± 1°C. 50 ± 0.1 g of 3.3 mass% saline was weighed out into a 100 mL beaker, a magnetic stir bar (8 mmφ × 30 mm without ring) was added, and the beaker was immersed in a thermostatic water bath to adjust the liquid temperature to 25 ± 0.2°C. Next, the beaker was placed on a magnetic stirrer and rotated at 600 rpm to generate a vortex in the salt water, and then 2.0 ± 0.002 g of water-absorbent resin particles were quickly added to the beaker, and the time (seconds) from the addition of the water-absorbent resin particles to the time when the vortex on the liquid surface converged was measured using a stopwatch. This time was taken as the water absorption rate of the water-absorbent resin particles.
[0100] [Method for measuring the swelling height H of water-absorbent resin particles in saline solution] The swelling height H of the saline solution one minute after the start of water absorption was measured using a swelling height measuring device. A schematic explanatory diagram of the swelling height measuring device is shown in Figure 1. The swelling height measuring device X shown in Figure 1 comprises a movement distance measuring device 1, a concave circular cup 2 (height of the inner part 30 mm, inner diameter 80.5 mm), a plastic convex circular cylinder 3 (outer diameter 80 mm, 60 through holes 7 with a diameter of 2 mm evenly arranged on the contact surface with the water-absorbent resin particles), and a nonwoven fabric 4 (thickness 0.1 mm, basis weight 10 g / m 2 The swelling height measuring device X is capable of measuring the distance change in units of 0.01 mm using a laser beam 6. The concave circular cup 2 is capable of uniformly dispersing a predetermined amount of water-absorbent resin particles. The convex circular cylinder 3 is capable of uniformly applying a load of 90 g to the water-absorbent resin particles 5. 0.5 g of sample (water-absorbent resin 5) is evenly spread in the concave circular cup 2, and nonwoven fabric 4 is laid on top of it. The convex circular cylinder 3 is gently placed on the nonwoven fabric 4, and the laser light 6 of the sensor of the movement distance measuring device 1 is set to the center of the cylinder 3. 55 g of 3.3 mass % saline solution adjusted to 20°C in advance is poured into the concave circular cup 2 over about 10 seconds so that the saline does not overflow from the concave circular cup 2, and the distance by which the water-absorbent resin particles 5 swell and push up the convex circular cylinder 3 is measured. One minute after the moment the water-absorbent resin particles start to absorb water (more precisely, the moment the water-absorbent resin particles absorb a very small amount of saline and push up the cylinder 3 by 0.5 mm), the distance by which the convex circular cylinder 3 is pushed up (including the height (0.5 mm) by which the cylinder 3 is pushed up at the moment when the water absorption starts) is recorded as the value of "saline swelling height H".
[0101] [Table 1]
[0102] Table 1 shows the saline water absorption amount (g / g), saline water absorption speed (sec), and saline swelling height H (mm / 0.5g) of the water absorbent resins obtained in each Example and Comparative Example. Table 1 also shows the amount of post-crosslinking agent used in the production of the water absorbent resins, and the moisture content after drying treatment. From Table 1, it can be seen that all of the water-absorbent resins obtained in Examples 1 to 4 had a saline swelling height H of 3.5 mm / 0.5 g or more, which indicates that the saline water absorption amount (g / g) was high and the saline water absorption speed (sec) was also fast. In contrast, in Comparative Examples 1 to 3 and 5, both the amount of post-crosslinking agent used and the water content were not within the appropriate range, so that the saline swelling height H was below 3.5 mm / 0.5 g, and the desired water absorption performance could not be obtained. In Comparative Example 4, the water absorbent resin was not granular but close to spherical, so that the desired water absorption performance could not be obtained.
Claims
1. A water-absorbing resin comprising partially neutralized polyacrylic acid, The polyacrylic acid has a crosslinked structure, the content ratio of acrylic acid salts relative to the total number of moles of all monomer components constituting the polyacrylic acid is 30 to 80 mol %, and the content ratio of monomer units other than acrylic acid and its salts contained in the polyacrylic acid is 5 mol % or less; A water-absorbent resin having a swelling height of 4.3 mm / 0.5 g or more and 6.0 mm / 0.5 g or less in 3.3 mass % saline solution measured under the following measurement conditions. (Conditions for measuring saline swelling height) 0.5 g of water-absorbent resin particles are scattered in a concave circular cup having a height of 30 mm and an inner diameter of 80.5 mm, a nonwoven fabric is laid on top of the particles, a convex circular cylinder having an outer diameter of 80 mm is placed on the nonwoven fabric, and 55 g of 3.3 mass % saline solution at 20° C. is poured into the concave circular cup. One minute after the water-absorbent resin particles start to absorb water, the distance by which the water-absorbent resin particles swell and push up the convex circular cylinder is measured, and this measured value is regarded as the saline swelling height of the water-absorbent resin.
2. 2. The water-absorbent resin according to claim 1, wherein the swelling height is 5.0 mm / 0.5 g or less.
3. A water-stopping material comprising the water-absorbent resin according to claim 1 or 2.
4. Step 1: A process for obtaining a partially neutralized polyacrylic acid by performing reverse phase suspension polymerization of a monomer component containing acrylic acid and a salt thereof and then drying the polymer; Step 2 of mixing the polyacrylic acid with a post-crosslinking agent to post-crosslink the polyacrylic acid; Including, the content of monomers other than acrylic acid and salts thereof in the monomer component is 5 mol % or less, In the step 1, the polyacrylic acid is dried so that the water content is 18.0 to 30 mass%, and in the step 2, an amount of a post-crosslinking agent used is 0.35 millimoles or more per mole of a total amount of the monomer components.
Citation Information
Patent Citations
Water-absorbing resin particles, water blocking material, power cable, communication cable, and method of producing water-absorbing resin particles
JP2016035060A
Water-absorbing resin particle excellent in salt resistance
JP2017179382A
Process for production of water-absorbing resin particles
WO2004083284A1
Process for production of water-absorbable resin
WO2007126002A1
Process for production of water-absorbing resin paticles, water-absorbing resin particles, water-stopping material, and absorbent article
WO2011065368A1